Simple induction Proof ------------------------- Claim: The sum of the first n odd numbers is equal to n^2 Base case (n=1): the sum of the 1 odd numbers is just 1 = 1^2 Inductive Hypothesis: Assume the claim is true for k. Inductive step: We wish to prove the claim for k+1. Proof: From the induction hypothesis, we know that the sum of the first k numbers is k^2. We also know the (k+1)th odd number is equal to 2k+1. So the sum of the first k+1 odd numbers is k^2 + 2k + 1 = (k+1)^2. Thus, proving the claim for k+1. Therefore, because we could have picked any value integer value of k for k>=1, the claim is true for all n >= 1. ------------------------------------------------------------ A more mathematical way ------------------------------------------------------------ Claim: From i = 1 to n, sum(2i-1) = n^2 Base case (n=1): sum(1) = 1 = 1^2 Inductive hypothesis: Assume the claim is true for k. Inductive step: We wish to prove the claim for k+1: From i=1 to k+1, sum(2i-1) = From i=1 to k, sum(2i-1) + 2(k+1)-1 = k^2 + 2(k+1) - 1 <--Induction hypothesis = k^2 + 2k + 1 = (k+1)^2 Therefore, by induction, the claim is true for all k >= 1.